A revised checklist of the genus Eupanacra Cadiou & Holloway, 1989 (Lepidoptera: Sphingidae) from China based on morphological and phylogenetic analyses - Jiang, Zhuo-Heng; Wang, Jia-Xin; Xu, Xiao-Dong; Wang, Xu; Hu, Shao-Ji (Zootaxa, 2026)
The taxonomy of the hawkmoth genus Eupanacra Cadiou & Holloway, 1989 (Lepidoptera, Sphingidae, Macroglossinae, Macroglossini) from China is reviewed based on differences of wing pattern, male and female genitalia, and phylogenetic relationships derived from analysis of DNA barcodes. Eupanacra tsekoui (Clark, 1926) stat. nov. is elevated to a full species. A new record of China, Eupanacra frena Swinhoe, 1892 is reported from Yingjiang, Yunnan. Distribution maps, biological notes and living records of Eupanacra from China are also given.